The militarization of justice: a state response to social protest (1949-1974) (2012)
This article aims to analyze the militarization of justice and state response to social protest in two periods in the history of Colombia's civil and military dictatorship (1949 - 1957) and the National Front (1958-1974). To do this, we study the evolution of military criminal justice in relation to two crucial aspects, namely, the criminalization of the strike as a political offense and the trial of civilians in military courts reasoned expressions of social discontent.